Therapeutic Drug Monitoring of Quinidine in Pediatric Patients with KCNT1 Genetic Variants - Alessandro Ferretti; Raffaele Simeoli; Sara Cairoli; Nicola Pietrafusa; Marina Trivisano; Carlo Dionisi Vici; Nicola Specchio; Bianca Maria Goffredo (MDPI AG, 2022)
Quinidine (QND) is an old antimalarial drug that was used in the early 20th century as an antiarrhythmic agent. Currently, QND is receiving attention for its use in epilepsy of infancy with migrating focal seizures (EIMFS) due to potassium sodium-activated channel subfamily T member 1 (KCNT1) genetic variants. Here, we report the application of Therapeutic Drug Monitoring (TDM) in pediatric patients carrying KCNT1 genetic variants and orally treated with QND for developmental and epileptic encephalopathies (DEE). We measured plasma levels of QND and its metabolite hydroquinidine (H-QND) by using a validated method based on liquid chromatography coupled with mass spectrometry (LC-MS/MS). Three pediatric patients (median age 4.125 years, IQR 2.375-4.125) received increasing doses of QND. Cardiac toxicity was monitored at every dose change. Reduction in seizure frequency ranged from 50 to 90%. Our results show that QND is a promising drug for pediatric patients with DEE due to KCNT1 genetic variants. Although QND blood levels were significantly lower than the therapeutic range as an anti-arrhythmic drug, patients showed a significant improvement in seizure burden. These data underlie the utility of TDM for QND not only to monitor its toxic effects but also to evaluate possible drug-drug interactions.